Contemporary treatment of renovascular hypertension - A.V. Khokhlov; M.V. Shymanko; A.O. Maksakov; M.V. Stan; K.S. Boiko; V.Yu. Kundin (Кардіохірургія та інтервенційна кардіологія)
The manuscript reviews the prevalence, methods of treatment, complications, morbidity, and mortality of patients with renovascular hypertension. According to current guidelines, there are three interrelated strategies for treatment of renovascular hypertension: antihypertensive drug therapy (angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers and calcium antagonists), invasive (percutaneous transluminal renal angioplasty and stenting) and surgical (revascularization or nephrectomy) treatment. The data of uncontrolled studies suggest that renal artery angioplasty or stenting provide a significant reduction of systolic blood pressure and improvement of chronic renal failure.